SUHU ANNEALING PRIMER INTER SIMPLE SEQUENCE REPEAT (ISSR) PADA DNA Aglaonema pictum (Roxb.) Kunth - Baharuddin, Muh. Fikry; Hariri, Muhammad Rifqi; Turhadi, Turhadi (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2026)
Aglaonema pictum is one of the most popular ornamental plants in the community. However, studies on the genetic diversity of A. pictum are still limited. Based on this, it is necessary to study the genetic diversity of A. pictum, one of which uses DNA-based markers such as Inter Simple Sequence Repeats (ISSR). In order to study of genetic diversity of A. pictum effectively and efficiently, one of the efforts that can be done is optimizing the annealing temperature for ISSR primers to be used. The purpose of this study was to optimize the effective Inter Simple Sequence Repeats (ISSR) primers on DNA of A. pictum. The methods used include DNA extraction using cetyltrimethylammonium bromide (CTAB), DNA amplification using primers ISSR1, ISSR2, ISSR3, ISSR4, ISSR5, ISSR6, ISSR7, ISSR8, ISSR9, ISSR10, ISSR11, and ISSR12) using Polymerase Chain Reaction (PCR) at temperature ranges of 52-54 ˚C. The results showed that ten out of 12 ISSR primers could amplify the DNA of A. pictum using optimal annealing temperatures. ISSR primers which identified optimum annealing temperature were ISSR1, ISSR3, ISSR5, ISSR6, ISSR7, ISSR8, ISSR9, ISSR10, ISSR11, and ISSR12. Primer of ISSR1 and ISSR11 showed optimum annealing temperature at 52,6°C. Primer of ISSR3, ISSR8, and ISSR9 showed optimum annealing temperature at 53,6°C, while primer of ISSR6, ISSR7, and ISSR10 showed optimum annealing temperature at 54°C. in other hands, primer of ISSR2 nad ISSR4 did not yet identified their optimum annealing in all tested temperature range. Kata kunci : Aglaonema pictum, Annealing Temperature, Genetic Diversity, Inter Simple Sequence Repeats